REPOSITORY OF GAS HYDRATES (Academic journal Industrial Machine Building Civil Engineering, 2017)
The article considers technology of production of gas hydrate with purpose it transportation and storage. The optimal parameters defined of storage of hydrates in terrestrial repositories at the nonequilibrium the conditions and melting of blocks with the internal source of energy preserved with ice crust. During research of kinetics of dissociation of samples of gas hydrate with the internal source of energy preservation with ice crust established that most of blocks to the moment of full dissociation long time was in the nonequilibrium conditions. In the process of dissociation of the samples was fixed effect self-preservation, melting of the surface of ice crust and freezing its basics. The dependence that describes the correlation-regressive relation between a surface area of hydrate block and the difference between fugacity of gas in the three-phase equilibrium and free gas was installed.The proposed gas hydrate technology makes it possible to solve the problem of diversification of sources of natural gas supplies, the development of a large number of small and medium sized remote gas deposits (including being in the form of gas hydrate), efficient use of resources associated gas, of shale gas and coal bed methane, and gas supply consumers in the absence of the pipeline.
Keywords: storage of gas; hydrate technology; gas hydrate block; self-preservation; icy crust; dissociation; equilibrium conditions